2018
DOI: 10.3390/w10081050
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Drainage System in the Lower Ablation Area of a Monsoonal Temperate Debris-Covered Glacier in Mt. Gongga, South-Eastern Tibet

Abstract: Seasonal evolution of the subglacial drainage system in the lower ablation area of the Hailuogou glacier ice tongue were revealed by repeated dye tracer (Rhodamine WT) experiments during the 2009 ablation season. Between April and October, 18 dye tracer experiments were conducted by injecting the tracer at one location of the lower ablation area of the Hailuogou Glacier to diagnose the seasonal variation of the subglacial drainage system of this section of glacier ice tongue. Using a simple advection-dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…Because the evolution of paraglacial slopes is closely related to glacier dynamics (Ballantyne and Benn, 1994;Ballantyne, 2002), we analysed the geomorphological processes and implications of retreat, thinning, and slowdown of the HLG and their relationships with PSF development. Detailed mapping of the retreat and thinning of the HLG over past decades has been well documented and reported (Li et al, 2010;He et al, 2008;Liu et al, 2018;Zhang et al, 2010;.…”
Section: Glacier Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the evolution of paraglacial slopes is closely related to glacier dynamics (Ballantyne and Benn, 1994;Ballantyne, 2002), we analysed the geomorphological processes and implications of retreat, thinning, and slowdown of the HLG and their relationships with PSF development. Detailed mapping of the retreat and thinning of the HLG over past decades has been well documented and reported (Li et al, 2010;He et al, 2008;Liu et al, 2018;Zhang et al, 2010;.…”
Section: Glacier Dynamicsmentioning
confidence: 99%
“…In addition to being seismically active, the combination of high rates of glacier ablation and abundant monsoonal precipitation and steep topography make the SETP highly susceptible to cryospheric hazards (Yao et al, 2019a), such as glacial debris flow, ice/snow avalanche, glacier-related landslide, and glacial lake outburst flood (Fan et al, 2019;Cheng et al, 2010;Xu et al, 2012). For example, at least four glacier-related landslides (1990He et al, 2008;Pan et al, 2012;Cao et al, 2019;Liu et al, 2018; and 12 glacial lake outburst floods (1931Yao et al, 2014) have been recorded across the SETP, and it has been suggested that more than half of the debris flows recorded in the SETP were cryogenic (Hu et al, 2011). Mass movements resulting from large-scale slope failures routinely form temporary valley-blocking natural dams (W. , behind which large lakes can develop and eventually outburst.…”
Section: Introductionmentioning
confidence: 99%
“…Gongga (Liu and Zhang, 2017), but only five exceed 10 km in length (Li et al, 2010). The temperate glaciers in these regions are known for high mass turnover and high ice flow velocity due to high ablation and high accumulation simultaneously in summer (Aizen and Aizen, 1994;Liu et al, 2018;Su and Shi, 2000). The climate of HLG catchment is characterized by southwest (India and Bengal monsoons) and southeast monsoons, which dominate during the summer (wet season), and by the westerly circulation, which dominates during the winter (dry season) (Li et al, 2010;.…”
Section: Study Areamentioning
confidence: 99%
“…It is the highest peak of the Hengduan Mountains, with an elevation of 7556 m. There are 74 glaciers around the main peak. The largest glacier is the Hailuogou Glacier on the eastern slope, which is ≈13 km long, 250-1200 m wide, and covers an area of 24.7 km 2 [37]. It is the most famous glacier in this area, and also a national scenic spot in China, which is visited by many tourists throughout the year.…”
Section: Overview Of the Study Areamentioning
confidence: 99%